2018
DOI: 10.1111/andr.12562
|View full text |Cite
|
Sign up to set email alerts
|

Radiation effects on male fertility

Abstract: Background: Spermatogenesis is a process of dynamic cell differentiation. Ionizing radiation impairs spermatogenesis, and spermatogonia are more radiosensitive than spermatocytes or spermatids. Consistent with this assumption and due to improvement in tumor curability, nowadays, fertility preservation represents a public health need. Objectives: To discuss radiotherapy-induced risk to male fertility and raise oncologic awareness of male fertility in daily clinical practice. Materials and Methods: PubMed and Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 15 publications
4
44
1
Order By: Relevance
“…Exposure to a threshold of 0.1 Gy of ionizing radiation caused significant decrease in sperm parameters, which was reversible after 9-18 months. However, exposure to > 3 Gy caused permanent infertility [84]. Considering the extreme sensitivity of the testicular tissue to radiation-induced damages, it is a common practice to use lead shields to minimize the exposure to testes during radiotherapy.…”
Section: Radiationmentioning
confidence: 99%
“…Exposure to a threshold of 0.1 Gy of ionizing radiation caused significant decrease in sperm parameters, which was reversible after 9-18 months. However, exposure to > 3 Gy caused permanent infertility [84]. Considering the extreme sensitivity of the testicular tissue to radiation-induced damages, it is a common practice to use lead shields to minimize the exposure to testes during radiotherapy.…”
Section: Radiationmentioning
confidence: 99%
“…Speiser et al assessed ten patients who received daily testicular doses of 0.12 Gy for a total dose of 1.4 -3.0 Gy ; all such patients had azoospermia, but only two of them for longer than 16 months 30) . De Felice et al reported that doses of irradiation > 0.35 Gy caused azoospermia, which was reversible in some cases 31) . The time taken for recovery increases with larger doses ; complete recovery takes place within 9 -18 months following radiation with < 1 Gy, but doses in excess of 2 -6 Gy may result in permanent azoospermia 31) .…”
Section: Human Studiesmentioning
confidence: 99%
“…De Felice et al reported that doses of irradiation > 0.35 Gy caused azoospermia, which was reversible in some cases 31) . The time taken for recovery increases with larger doses ; complete recovery takes place within 9 -18 months following radiation with < 1 Gy, but doses in excess of 2 -6 Gy may result in permanent azoospermia 31) . According to the International Atomic Energy Agency (IAEA), a dose of 1.0 Gy leads to a temporary reduction in the number of spermatozoa, that of 1.5 Gy leads to temporary sterility, and that of 5.0 to 6.0 Gy (acute) can produce permanent sterility in males 32) .…”
Section: Human Studiesmentioning
confidence: 99%
See 2 more Smart Citations